2001
DOI: 10.1042/bj3550489
|View full text |Cite
|
Sign up to set email alerts
|

Identification, characterization and leucocyte expression of Siglec-10, a novel human sialic acid-binding receptor

Abstract: Here we characterize Siglec-10 as a new member of the Siglec family of sialic acid-binding Ig-like lectins. A full-length cDNA was isolated from a human spleen library and the corresponding gene identified. Siglec-10 is predicted to contain five extracellular Ig-like domains and a cytoplasmic tail containing three putative tyrosine-based signalling motifs. Siglec-10 exhibited a high degree of sequence similarity to CD33-related Siglecs and mapped to the same region, on chromosome 19q13.3. The expressed protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 36 publications
(77 reference statements)
1
56
1
Order By: Relevance
“…The preference of sialoadhesin (mSiglec-1) and MAG (mSiglec-4) for the NeuAc␣(2-3)Gal sequence over the NeuAc␣(2-6)Gal sequence (26,27,30,32,34,36) is consistent with the 2-3-and 5-7-fold increased affinity, respectively, for sialosides with the ␣2-3 linkage (4 and 5) over those with the ␣2-6 linkage (12 and 13), in good agreement with results obtained by Strenge et al (26). A preference of Siglecs-9 and -10 for sialosides with the ␣2-3 linkages seen here (1.5-2-fold) was not recognized previously using multivalent probes (51,53,59,61). Yamaji et al (28) demonstrated a unique preference of Siglec-7 for the NeuAc␣(2-8)NeuAc sequence found in the ganglioside GD3 based on competitive inhibition of binding to a multivalent GD3-bovine serum albumin probe using ganglioside micelles.…”
Section: Potent Inhibition Of Mag (Siglec-4) By O-linked Sialosides-tocontrasting
confidence: 44%
See 1 more Smart Citation
“…The preference of sialoadhesin (mSiglec-1) and MAG (mSiglec-4) for the NeuAc␣(2-3)Gal sequence over the NeuAc␣(2-6)Gal sequence (26,27,30,32,34,36) is consistent with the 2-3-and 5-7-fold increased affinity, respectively, for sialosides with the ␣2-3 linkage (4 and 5) over those with the ␣2-6 linkage (12 and 13), in good agreement with results obtained by Strenge et al (26). A preference of Siglecs-9 and -10 for sialosides with the ␣2-3 linkages seen here (1.5-2-fold) was not recognized previously using multivalent probes (51,53,59,61). Yamaji et al (28) demonstrated a unique preference of Siglec-7 for the NeuAc␣(2-8)NeuAc sequence found in the ganglioside GD3 based on competitive inhibition of binding to a multivalent GD3-bovine serum albumin probe using ganglioside micelles.…”
Section: Potent Inhibition Of Mag (Siglec-4) By O-linked Sialosides-tocontrasting
confidence: 44%
“…Several reports (25,26,28,39,40) have evaluated the specificity of one or several siglecs using competitive inhibition of multivalent binding assays by monovalent sialosides analogous to the studies reported here. However, most have used multivalent assays based on binding of siglecs to sialosides attached to a polyacrylamide or other polymeric carrier (1,34,37,49,(52)(53)(54)(55)(57)(58)(59), to gangliosides adsorbed to microtiter plates (30,36,38) or to neo-glycoprotein conjugates (27,28).…”
Section: Figmentioning
confidence: 99%
“…16 These mice develop a B-cell hyperplasia of the CD5 + lineage in the peritoneal cavity that evolves into a frank B-cell leukemia/lymphoma with variable penetrance (from 10% annually in Eµ-BRD2 mice to 100% in Eµ-TCL1 mice) and at different ages (from 7 months in Eµ-BRD2 mice to 12-18 months in CLL mouse models). Such heterogeneous evolution indicates that the expansion and progression of malig- Federico Caligaris-Cappio, 1,7,8 and Paolo Ghia…”
Section: Q14-minimal Deleted Region (Mdr)mentioning
confidence: 99%
“…We also analyzed T lineage cells over time, although T-SIGLEC-G deficiency promotes B-cell lymphoma haematologica | 2014; 99 (8)cell numbers were reportedly stable in 2-to 3-month old Siglecg −/− mice. 1 In accordance with this previous report, the percentage of splenic CD3 + T cells was unmodified at 5, 10 and 16 months of age.…”
Section: Cd5mentioning
confidence: 99%
See 1 more Smart Citation